Patterns of protein and carbohydrate accumulation during somatic embryogenesis of Acca sellowiana - Cangahuala-Inocente, Gabriela Claudia; Steiner, Neusa; Maldonado, Sara Beatriz; Guerra, Miguel Pedro (Pesquisa Agropecuaria Brasileira, 2010)
The aim of this work was to quantify the protein, starch and total sugars levels during histodifferentiation and development of somatic embryos of Acca sellowiana Berg. For histological observations, the samples were dehydrated in a battery of ethanol, embedded in historesin and stained with toluidine blue (morphology), coomassie blue (protein bodies) and periodic acid–Schiff (starch). Proteins were extracted using a buffer solution, precipitated using ethanol and quantified using the Bradford reagent. Total sugars were extracted using a methanol-chloroform-water (12:5:3) solution and quantified by a reaction with anthrone at 0.2%. Starch was extracted using a 30% perchloric acid solution and quantified by a reaction with anthrone at 0.2%. During the somatic embryogenesis’ in vitro morphogenesis and differentiation processes, the total protein levels decreased and the soluble sugars levels increased during the first 30 days in culture and remained stable until the 120th day. On the other hand, total protein levels increased according to the progression in the developmental stages of the somatic embryos. The levels of total sugars and starch increased in the heart and cotyledonary stages, and decreased in the torpedo and pre-cotyledonary stages. These compounds play a central role in the development of somatic embryos of Acca sellowiana.